Classification of the Charcot neuroosteoarthropathy: evolution of views and unsolved problems - V. B. Bregovskiy; S. A. Osnach; V. N. Obolenskiy; A. G. Demina; A. L. Rybinskaya; V. G. Protsko (Сахарный диабет)
Diabetic Charcot neuroosteoarthropathy is a manifestation of diabetic foot syndrome, accompanied by a high risk of foot ulcers and amputation. Many aspects of this pathology due to its features remain poorly understood, which leads to difficulties in determining the tactics of treatment of these patients. This review analyzes of anatomical and functional classifications of Charcot foot. The review focuses on the midfoot pathology as the most severe in their consequences. The advantages and disadvantages of different approaches to the description of the X-ray picture of the disease at its various stages are analyzed. The systematization of the literature allows us to conclude that the existing approaches to classification are relatively acceptable mainly when planning conservative treatment. At the same time, detailed anatomical and radiological classifications do not help in choosing the tactics of reconstructive surgical treatment. With the increasing availability of reconstructive surgery for severe deformities due to Charcot’s arthropathy, it seems appropriate to develop classification systems that could become a practical tool for determining surgical tactics in this pathology.